LMS-based digital background mismatch calibration technique for SAR ADC. (June 2023) - Wan, Jing; Song, Shida; Liang, Yuhua
Abstract: This paper proposes a digital background calibration technique based on the Least Mean Square (LMS) algorithm to suppress non-linearity in the SAR ADC. The calibration scheme does not significantly increase the complexity or scale of analog circuits. To evaluate the effectiveness of the proposed calibration scheme, we conducted 200-run Monte-Carlo simulations of a multi-segmented 20-bit SAR ADC using MATLAB. The simulation results demonstrate that the average values of SFDR and THD significantly improve from 60.9 dB and −59.2 dB–130 dB and −129.5 dB, respectively, under 1% capacitor mismatch. It is indicated that the proposed calibration scheme can significantly enhance the linearity of the SAR ADC.